Wound care during the COVID-19 pandemic: improving outcomes through the integration of telemedicine. (1st April 2021) - Oropallo, Alisha; Lantis, John; Martin, Alexander; Rubaiay, Ammar Al; Wang, Na
Abstract : COVID-19 is highly contagious and its rapid spread burdens the healthcare system. As the number of confirmed cases goes up, the shortage of medical resources has become a challenge. To avoid the collapse of the healthcare system during the fight with COVID-19, all healthcare workers, including wound care practitioners, should adapt to new roles and use any appropriate methods available to slow the spread of the virus. Integrating telemedicine into wound care during the outbreak helps maintain social distancing, preserve personal protective equipment and medical resources, and eliminate unnecessary exposure for both vulnerable patients and high-risk healthcare workers.